2016
DOI: 10.2298/apt1647177c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of steeping time on biological activity of black mulberry leaves tea

Abstract: Black mulberry leaves teas (BMLTs) were prepared using boiled water and different steeping time (5 10, 20, 35 and 45 minutes). In order to establish the connection between steeping time and tea quality, total phenolics content (TPC), total flavonoids content TFC contents were measured, as well as two antioxidant assays (DPPH and reducing power assays), alone with antimicrobial and cytotoxic tests. The obtained results showed that TPC, TFC, IC 50 and EC 50 values increased with the increase in steeping time, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…The phenolic acids as chlorogenic acid, syringealdehyde, vanillic acid, m‐ coumaric acid, p‐ hydroxybenzoic acid, chlorogenic acid, syringic acid, p‐ coumaric acid, protocatechuic aldehyde were detected in M nigra leaves (Memon et al, ). In another study, Cestic et al () identified seven phenolic compounds (gallic acid, caffeic acid, sinapic acid, ferulic acid, vanillic acid, chlorogenic acid, and p ‐coumaric acid) in black mulberry leaves tea.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The phenolic acids as chlorogenic acid, syringealdehyde, vanillic acid, m‐ coumaric acid, p‐ hydroxybenzoic acid, chlorogenic acid, syringic acid, p‐ coumaric acid, protocatechuic aldehyde were detected in M nigra leaves (Memon et al, ). In another study, Cestic et al () identified seven phenolic compounds (gallic acid, caffeic acid, sinapic acid, ferulic acid, vanillic acid, chlorogenic acid, and p ‐coumaric acid) in black mulberry leaves tea.…”
Section: Resultsmentioning
confidence: 99%
“…The mulberry plant, which belongs to the genus Morus of the Moraceae family, has been cultivated widely in India, China, Japan, Pakistan, Iran, Tunusia, Korea, Mexico, Brazil, Spain, including Turkey (Cestic, Radojkovic, Cvetanovic, Maskovic, & Durovic, ; Ercişli & Orhan, ; Thabti, Elfalleh, Hannachi, Ferchichi, & Campos, ). There are 24 species of Morus .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations